Digitalizing Quality Management in Islamic Boarding Schools: An Application of the Deming Framework - Mohammad Mas'ud; Moh Khusnuridlo; Moh Anwar (JURNAL AL-TANZIM, 2026)
This study aims to examine the educational quality management cycle in the digital transformation of Islamic boarding schools based on the Deming framework. This research used a qualitative approach with a multiple-case study design. Data were collected through in-depth interviews, observation, and documentation, then analyzed using an interactive data analysis model. The results indicate that the digital quality planning stage begins with the development of an institutional information platform and communication system to increase transparency and administrative efficiency. During the implementation phase, Islamic boarding schools deploy various digital services, including online student registration, an alum tracking system, a financial services platform, and an institutional data management system that supports educational operations. Quality evaluation is conducted through a data-driven monitoring system that allows administrators to assess program effectiveness and alumni development more measurably. Furthermore, continuous improvement is realized through the integration of digital platforms and curriculum innovations that combine traditional Islamic boarding school values with modern educational management practices. This research contributes to the development of digital education management literature in faith-based institutions and recommends strengthening digital governance and sustainable technological innovation within Islamic boarding schools.